2022
DOI: 10.3390/biom12121786
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Type and Concentration Differently Affect Colon Cancer Cells Ultrastructural Morphology, EMT Markers, and Matrix Degrading Enzymes

Abstract: Aim of the study was to understand the behavior of colon cancer LoVo-R cells (doxorubicin-resistant) vs. LoVo-S (doxorubicin sensitive) in the initial steps of extracellular matrix (ECM) invasion. We investigated how the matrix substrates Matrigel and type I collagen-mimicking the basement membrane (BM) and the normal or desmoplastic lamina propria, respectively-could affect the expression of epithelial-to-mesenchymal transition (EMT) markers, matrix-degrading enzymes, and phenotypes. Gene expression with RT-q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…In particular, we investigated the behavior of LoVo-S and LoVo-R cells growing in ECM substrates covering Millipore filters, which did not mechanically allow them to invade after 24 h. We found that when low aggressive LoVo-S cells were hindered to cross the Millipore filter and only tried to invade a concentrated type I Collagen substrate (3.5 mg/mL) they developed a morphological and biomolecular EMT phenotype. Surprisingly, the more aggressive doxorubicin-resistant LoVo-R cells appeared independent on TME, because they did not change their morphological phenotype, EMT markers, and HPSE expression in all the different tested ECM substrates [26].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In particular, we investigated the behavior of LoVo-S and LoVo-R cells growing in ECM substrates covering Millipore filters, which did not mechanically allow them to invade after 24 h. We found that when low aggressive LoVo-S cells were hindered to cross the Millipore filter and only tried to invade a concentrated type I Collagen substrate (3.5 mg/mL) they developed a morphological and biomolecular EMT phenotype. Surprisingly, the more aggressive doxorubicin-resistant LoVo-R cells appeared independent on TME, because they did not change their morphological phenotype, EMT markers, and HPSE expression in all the different tested ECM substrates [26].…”
Section: Discussionmentioning
confidence: 91%
“…Data obtained after 24 h from these free-migrating cells were compared with the results reported in a previous study, where LoVo cells were cultivated for 24 h on the same ECM substrates covering a Millipore filter whose pore size stopped cell migration [26]. After 24 h, the freedom of movement attenuated LoVo-S cells' aggressiveness by reducing all the MMPs in both LoVo-S and -R cells cultivated in any substrate.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Their role includes maintaining hypoxia in the TME and cross-linking collagen fibers, causing ECM stiffness and, consequently, its degradation. The consequence is the proliferation of cancer cells, their release from the niche, and migration [242,243]. The ECM reorganization induced by reduced elasticity of fibers is mainly a consequence of reprogrammed niche cells depositing larger amounts of collagen, primarily type I as well as II, III, IV, and IX.…”
Section: Degradation Of the Extracellular Matrix In The Crc Microenvi...mentioning
confidence: 99%
“…Furthermore, MMPs, including MMP9 and MMP14, may confer resistance to various cancer therapies by altering tumor vasculature to impact drug delivery, promoting survival pathways in cancer cells, or driving the acquisition of more aggressive phenotypes through EMT [ 173 , 174 , 175 ]. The specific MMPs implicated in therapy resistance may depend on the type of treatment administered.…”
Section: Tumor Budding and Its Influence On The Tumor Stroma In Crcmentioning
confidence: 99%